Correction: Electrocatalytic oxidation of benzyl alcohol for simultaneously promoting H2 evolution by a Co0.83Ni0.17/activated carbon electrocatalyst. (8th May 2019) - Liu, Guoqiang; Zhang, Xian; Zhao, Cuijiao; Xiong, Qizhong; Gong, Wanbing; Wang, Guozhong; Zhang, Yunxia; Zhang, Haimin; Zhao, Huijun
Abstract : Correction for 'Electrocatalytic oxidation of benzyl alcohol for simultaneously promoting H2 evolution by a Co0.83 Ni0.17 /activated carbon electrocatalyst' by Guoqiang Liu et al., New J. Chem., 2018, 42, 6381–6388.